The Consensual Methods of Dispute Resolution Applied to the New Law on Public Procurement and Administrative Contracts (Research, Society and Development, 2022)
The bidding procedure is fundamental for Public Administration and, therefore, has been undergoing improvements in recent decades. Due to this concern, in 2021 the new regulatory framework for public procurement and contracting was published which seeks to gather the basic and essential qualifications for the establishment, execution of the bidding process and the inspection of contracts in a more efficient way. This article aims to describe the consensual forms of conflict resolution provided for in the new bidding law and to identify the benefits that these methods can bring to the Public Administration in the execution of acquisitions and contracts. As a result of the present study, it was possible to observe that the application of consensual methods of conflict resolution, even from a theoretical point of view, has the potential to provide speed in the resolution of problems, reduction of conflicts between the Administration and the contractors and economy in court proceedings.